Impact of CO(2) on Pyrolysis Products of Bituminous Coal and Platanus Sawdust - Luo, Ying (Polymers (Basel), 2019)
Abundant studies have been completed about factors on the pyrolysis of coal and biomass. However, few articles laid emphasis on using CO(2) as a carrier gas to explore the compositional changes of pyrolysis products in coal and biomass pyrolysis for industrial application and commercial value. The experiments on coal and biomass pyrolysis in N(2) and CO(2) using a horizontal tube furnace were conducted at 500 °C. The impact of introducing CO(2) on the pyrolysis process of bituminous coal and Platanus sawdust was investigated. The nuclear magnetic resonance (NMR) spectra of tar and the characterizations of char including Brunner-Emmet-Teller (BET) measurements, scanning electron microscope (SEM), Fourier transform infrared (FT-IR) spectroscopy, and element analysis were studied. The findings in light of the experimental results show that introducing CO(2) enhances the coal and biomass pyrolysis in a solid product by promoting the fracture of hydroxyl groups. It also promotes tar decomposition and the release of volatiles, which contribute to the occurrence of char with high porosity, pore volume, and specific surface. Furthermore, higher specific surface enhances the adsorption performance of char as active carbon. Simultaneously, CO(2) promotes the increase of oxygen-containing aromatics especially the methoxy-containing aromatics, and the decrease of deoxygenated aromatic hydrocarbons in pyrolysis oils. In addition, the introduction of CO(2) changes the amount of aliphatic compounds in various ways for the pyrolysis of coal and biomass. From a perspective of business, the changes in the composition of pyrolysis oil brought by CO(2) may create new value for fuel utilization and industrial products.